Efforts to Overcome Early Reading Difficulties Through Traditional Game-Based Picture Series Media for Grade 2 Elementary School Students - Asiah; Iis Nurasiah; Din Azwar Uswatun (Institut Agama Islam Negeri (IAIN) Curup, 2026)
The background of this study is the low level of beginning reading skills of grade II elementary school students so that improvements need to be made to improve beginning reading skills. The purpose of this study was to improve the ability of beginning reading in grade II elementary school students through the use of traditional game-based serial picture media. The subjects of this study were grade II elementary school students at SD Negeri Karyautama totaling 24 students. The research method used was Kemmis and Mc Taggart design classroom action research. Data were collected through observation and tests then analyzed using Miles and Huberman techniques for qualitative data and descriptive statistical techniques for quantitative data. The results showed that in the pre-cycle the average value obtained was 68.75 with a percentage of classical completeness of 50% and included in the Fair criteria. In cycle I, it increased to 75.17 with the percentage of classical completeness reaching 62.50% and included in the good criteria. The beginning reading ability in cycle II increased again to 85.16 with a percentage of classical completeness of 91.76% and included in the excellent criteria. It can be concluded that the use of traditional game-based serial picture media can improve early reading skills.